Liberating Curriculum: A Pedagogy of Publicness that Counters Dominant Culture - Grant , Janelle (Journal of Public Pedagogies, 2022)
This paper explores critical public pedagogy in relation to narratives and teaching about mass incarceration in the United States. This paper uses Gert Biesta’s theorization about creating pedagogy in the interest of publicness to understand conceptions of public discourse and pedagogy in the interest of publicness. I explore the Liberation Arts Project (a Black-led art program founded by currently incarcerated people) as an example of counter pedagogy that calls for society to imagine a better, more inclusive and caring world despite historical tendencies to ignore social traumas that co-occur alongside racialized control and discipline.